The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.52627/ijeam.v2i3.43
|View full text |Cite
|
Sign up to set email alerts
|

Kepemimpinan Transformasional Kepala Sekolah Dan Komunikasi Organisasi Pengaruhnya Terhadap Komitmen Organisasi Guru

Abstract: This study was conducted to reveal the principal's transformational leadership and organizational communication its effect on teacher organizational commitment. This study uses a quantitative approach with a survey method with a total sample of 28 teachers. The data collection technique used a questionnaire with a Likert scale. Data were analyzed using simple and multiple correlation and regression techniques. The results of this study indicate that the principal's transformational leadership and organizationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to Russamsi et al (2020), principal leadership has been shown to enhance teacher professionalism and productivity. According to Zainuddin et al (2020), a principal's leadership combined with effective organizational communication can boost teacher commitment, enhancing performance. According to Endaryono et al (2021), democratic leadership style is recommended for school administrators.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…According to Russamsi et al (2020), principal leadership has been shown to enhance teacher professionalism and productivity. According to Zainuddin et al (2020), a principal's leadership combined with effective organizational communication can boost teacher commitment, enhancing performance. According to Endaryono et al (2021), democratic leadership style is recommended for school administrators.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Transformative leaders bear a significant level of responsibility since they consistently strive to achieve exceptional performance and assist members in times of difficulty. In a recent study conducted by (Zainuddin et al, 2020), the authors propose that transformative leadership is marked by a solid commitment to the organization's goals and objectives, as well as the establishment of a conducive work environment that facilitates the successful execution of planned work programmes.…”
Section: The Impact Of Idealism From the Headmastersmentioning
confidence: 99%
“…Oleh karena itu, kepala sekolah mesti flexibel, kreatif, dan berjuang serta memiliki tekad yang kuat, semangat dan cita-citanya kuat. Zainuddin (2020), memaparkan pemimpin transformasional yang sukses dalam pendidikan memaparkantujuh sikap utama, yang meliputi: mengidentifikasi diri sendiri sebagai agen perubahan; berani; mempercayai orang lain; bertindak selaras sistem yang berbasis nilai, bukan kekrusialan individu atau kelompok; terus menerus menaikan kecakapan; mampu menangani situasi yang kompleks dan tidak pasti; dan memiliki pandangan yang visioner. juga mencatat bahwa kepemimpinan transformasional merupakan pendekatan yang cocok bagi kepala sekolah untuk memimpin dan mengembangkan sekolah yang berkualitas tinggi.…”
Section: Landasan Teoriunclassified